Does Acute Kidney Injury Alter Energy Metabolism of Septic Patients? - Ana Cláudia Soncini Sanches; Cassiana Regina de Góes; Marina Nogueira Berbel Bufarah; André Luis Balbi; Daniela Ponce (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Background: The  determination  of  resting  energy  expenditure  (REE)  in  critically  ill  patients  is essential to prevent hypo and hyper alimentation. Objectives: This study aims to describe the REE in septic patients with and without acute kidney injury (AKI) and compare by examining the REE estimated by Harris-Benedict equation (HB) with the REE measured by indirect calorimetry (IC). Methods: Prospective study was performed in septic patients older than 18 years, undergoing mechanical ventilation, with or without AKI defined by KDIGO criteria, and admitted to the Intensive Care Unit of University Hospital. The REE was estimated by HB equation and measured by IC within 72 hours after the diagnosis of sepsis and seven days after the initial measure. Results: Sixty-eight  patients  were  evaluated,  age  was  62.49±16.6  years,  63.2%  had  AKI,  and SOFA was 9.81±2.35. The measured REE was 1857.53±685.32 kcal, while the estimated REE was 1514.87±356.72  kcal,  with  adequacy  of  123.49±43%.  Septic  patients  without  AKI  (n=25)  and  with AKI  (n=43)  had  measured  REE  statistically  higher  than  the  estimated  one  (1855  kcal  (1631.75-2052.75)  vs.  1551  kcal  (1349  -1719.25),  p=0.007  and  1868.0  kcal  (1219.5-2364.75)  vs.  388  kcal(1254-1665.5), p=0.026, respectively). There was no significant difference between the two groups in measured and estimated REE and in evolutional REE.